Individual counseling practice with solution-focused brief counseling in cross-cultural counseling - Aprila, Ana; Suarni, Ni Ketut; Dharsana, I Ketut (ProGCouns: Journal of Professionals in Guidance and Counseling, 2023)
Cross-cultural counseling refers to a therapeutic process that occurs between counselors and clients who originate from diverse backgrounds and cultural contexts. Hence, it is imperative for counselors to possess proficiency in the domain of cross-cultural counseling in their professional endeavors. This research employed a qualitative descriptive methodology to examine the cross-cultural counseling process using the solution-focused brief counseling approach. The study focused on a seventh-grade student from one of the public schools in Nusa Tenggara Timur Indonesia who belonged to a distinct cultural background from the counselor. The primary objective was to investigate the effectiveness and outcomes of the cross-cultural counseling process when implementing the solution-focused brief counseling approach. The study's findings indicate that individual counseling using the Focused Solution Brief Counseling technique encompasses several key components. These include the construction of a positive therapeutic relationship, goal setting, the identification of issues, the development and implementation of solutions, and the termination of the counseling session. The study additionally demonstrates that within the realm of cross-cultural counseling, the solution-focused brief counseling approach has the capacity to effectively address the challenges faced by students. Therefore, solution-focused brief counseling may serve as an effective strategy for school counselors that can help students resolve their problems.